Intracardiac yolk sac tumor in an infant girl - Graf, Matthias; Bläker, Hendrik; Schnabel, Philipp Albert; Serpi, Mario; Ulmer, Herbert E.; Otto, Herwart F. (Pathology, research and practice, 1999)
We report about a two and a half year old girl with a primary yolk sac tumor (YST) of the heart, located in the interventricular septum. The girl was admitted to the hospital with a systolic cardiac murmur. Echocardiography revealed a smoothly surfaced tumor which based on the interventricular septum below the aortic valve and filled out more than half of the left ventricular cavity. Diagnosis of a yolk sac tumor was established on a frozen section of a biopsy taken at surgery and confirmed by the examination of the resected material. Excessively elevated serum alpha-fetoprotein (AFP) levels contributed to this diagnosis. Follow up examinations of the patient including computed tomography (CT) of head, thorax and abdomen, did not indicate an extracardiac tumor manifestation. We found no previous report of a primary intracardial yolk sac tumor in the literature.